A Comparative Transcriptome Analysis Reveals the Effects of Letrozole and 17α-Methyltestosterone on the Expression of Reproductive-Related Genes in Golden Pompano (Trachinotus ovatus) - Qi Zhou; Yan Wang; Yuwen Guo; Guangli Li; Tao Wang; Huapu Chen (Fishes)
Aromatase inhibitor letrozole (LZ) and 17α-methyltestosterone (MT) are commonly used for sex control breeding to induce female-to-male sex reversal in aquaculture. However, studies on the molecular regulatory mechanisms of LZ and MT are still limited. Here, a comparative transcriptome analysis was conducted on the hypothalamus, the gonad, and the liver of golden pompano (Trachinotus ovatus) after 30 days of LZ and MT treatment, which demonstrated significant sexual size dimorphism. Following LZ treatment, the transcriptome data identified 156, 890, and 1286 different expression genes (DEGs) in the hypothalamus, the liver, and the gonad, respectively. After MT treatment, the transcriptome data identified 114, 876, and 950 DEGs in the hypothalamus, the liver, and the gonad, respectively. Functional enrichment analysis revealed that DEGs were involved in oocyte meiosis and steroid-hormone synthesis following LZ treatment. Similarly, the analysis indicated that DEGs were associated with cysteine and methionine metabolism and steroid-hormone synthesis after MT treatment. Further analysis showed that LZ treatment can promote the first meiotic division but inhibit the second meiotic division of the oocyte. MT treatment promotes polyamine synthesis to induce oocyte apoptosis, both of which affect the trajectory of ovarian differentiation in golden pompano. However, LZ and MT have converse effects in sex hormone synthesis. LZ inhibits estrogen metabolism but promotes cholesterol synthesis by regulating sqle, cyp3a40, ugt1a1, and ugt2a1, while MT promotes estrogen metabolism but inhibits the conversion of cholesterol to pregnenolone by regulating cyp19a1, cyp1a, and hsd17b7. This study reveals that both LZ and MT may inhibit the ovarian differentiation and induce masculinization through different regulatory mechanisms, which provides a fundamental insight into the sex control breeding in aquaculture.